DISEMINASI PRODUKSI BENIH KENTANG SISTEM AEROPONIK PADA KELOMPOK TANI HARAPAN BARU DI KECAMATAN LEMBAH GUMANTI KABUPATEN SOLOK - Irfan Suliansyah; Helmi Helmi; Fitri Ekawati; Doni Hariandi (Jurnal Hilirisasi IPTEKS, 2021)
Potato is a leading commodity in Alahan Panjang, Solok, West Sumatra. However, the existence of potatoes is increasingly limited due to the fewer farmers who cultivate this plant. The difficulty in obtaining quality seeds is the main reason farmers replace potatoes with other horticultural commodities. There is now a new potato breeding technology that promises higher seed production and seed quality. Aeroponics technology is a cultivation technology without using media. This technology relies on regular misting of water and nutrients into the root zone of the plant. However, this technology has not been applied by potato farmers in West Sumatra Province. The purpose of this activity is to develop a strategy for developing potato seed farming through an aeroponic system and empowering farmers to become producers of high-quality potato seeds through the development and transfer of technology for potato seed production in aeroponics so that farmers can meet their own seed needs within the framework of potato farming. This activity was carried out in Jorong Galagah, Alahan Panjang village, Lembah Gumanti District, Solok Regency. The implementation of the activity consists of two activities: 1) dissemination/socialization of activities and 2) demonstration of aeroponic potato seed production technology. The partner of this activity is the Harapan Baru Farmers Group. The Harapan Baru Farmers Group is one of the farmer groups in Alahan Panjang whose members are horticultural farmers, including potatoes. The results of the activity obtained by partner farmers are generally optimistic that they can carry out potato seed breeding with an aeroponic system independently after following the stages of training activities. This farmer group has applied bio cellular technology to produce potato seeds and use it for consumption potato production. With the application of aeroponic technology, it is expected that the productivity of potato seeds produced will be higher, and the quality of the seeds will also be better.